Primary Infertility secondary to Testicular Microlithiasis - Shah, Imtiaz; Khan, Fayaz; Zaieem, Mohammad; Khan, Farhan; Khan, Suhail; Koul, Avinash (Bangladesh Journal of Medical Science, 2017)
Testicular microlithiasis is an uncommon entity among adult males, resulting from tubular calcification. Reported incidence of testicular microlithiasis has been highly variable in the past decade due to increasing frequency of ultrasound examination of scrotal and testicular conditions. Testicular microlithiasis is associated with many benign and malignant conditions of testes. It is believed that in patients with Testicular microlithiasis conservative approach is warranted in absence of high risk factors, like contralateral testicular tumors, chromosomal anomalies and gonadal dysgenesis. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.178-180